The proportions and rates of economic activities as a factor of gross value added maximization in transition economy - Vyklyuk, Yaroslav; Yevdokymenko, Valeriy; Yaskal, Ihor (My University, 2016)
Sustain growth of value added is one of the most important problem in many countries with transition economy. The article provides new evidence about determining the future dynamics of the economic activities with increasing value added. In this paper, we have used Hopfield’s neural network to clarify the strategies of social and economic development of country. Three types of strategies have been created with using mathematical models and quantitative assessment of their efficiency has been made. From the simulation results, it is observed that state regulation based on this methodology can build the basis for further improvements in economic policy.
Keywords: gross value added; structure of economic activities; Hopfield’s network; strategy